Leading the counter-revolution: Saudi Arabia and the Arab Spring - Guido Steinberg (Stiftung Wissenschaft und Politik (SWP), 2014)
The Kingdom of Saudi Arabia has survived the revolutions in the Arab world largely unscathed and entrenched itself as the undisputed leader of the Arab monarchies and the wealthy oil- and gas-producing states. More broadly, though, Saudi and Gulf rulers' concerns about their restive populations meld with confessional tensions associated with the pre-existing conflict between Iran and its regional adversaries. Saudi Arabia and its allies interpret unrest among the Shiites in the Saudi Eastern Province and Bahrain not as protest movements against authoritarian regimes but as an Iranian plot to topple legitimate governments with the assistance of the Arab Shiites. Riyadh has long feared that Tehran aspires to hegemony in the Middle East, and has consequently been pursuing an increasingly determined anti-Iranian regional policy since 2005. Since spring 2011 Riyadh has adopted a twin-track approach. Firstly, the Saudis have worked to stabilise the Jordanian and Moroccan monarchies and backed the Egyptian military, making Saudi Arabia the central proponent of the authoritarian status quo (ante) in the region. Secondly, Riyadh has increasingly taken the offensive. In March 2011 Saudi Arabia led the United Arab Emirates, Kuwait and Qatar to rescue the Bahraini House of Khalifa after protests by Shiites threatened to spin out of control. The Saudis are operating even more decisively in Syria, where since September 2013 they have stepped up their supplies of money and arms to opposition and insurgent groups in order to bring about the fall of Iran's ally Assad. (SWP Research Paper)
Keywords: 320